Covalent organic framework composite membrane as well as preparation method and application thereof

By doping ionic covalent organic frame materials with different charged potentials with carbon nanotubes to prepare composite membranes, the complex problem of irregulating pore size of polymer membranes in the prior art is solved, and a composite membrane with high salt cutoff and flexibility is achieved, which is suitable for seawater desalination and dye separation.

CN119701655APending Publication Date: 2025-03-28HAINAN UNIV

Patent Information

Application Number
CN202411897024.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing amorphous polymer film lacks orderly and adjustable pore size, has low porosity, poor connectivity, and is not suitable for molecular transmission. The existing covalent organic frame composite film preparation method is complex, time-consuming and cost-effective, and is only suitable for gas separation, and its flexibility is not enough to support liquid separation.

Method used

The composite film was prepared by doping ionic covalent organic frame materials with different charged potentials with carbon nanotubes. The covalent organic frame nanosheets were synthesized in one step by the interface method, and the composite film was formed by vacuum pressurization.

Benefits of technology

The prepared composite membrane has excellent properties, including high salt cutoff and good flexibility, and is suitable for seawater desalination and dye separation, which is more cost-effective and has a wide range of application than the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701655A_ABST
    Figure CN119701655A_ABST
Patent Text Reader

Abstract

The invention provides a covalent organic framework composite membrane as well as a preparation method and application thereof. The preparation method of the covalent organic framework composite membrane comprises the following steps: (1) dissolving 2, 4, 6-triformyl phloroglucinol in an organic solvent to obtain a 2, 4, 6-triformyl phloroglucinol solution; slowly adding a buffer layer of deionized water or alkali liquor to the top of the 2, 4, 6-triformyl phloroglucinol solution; dropwise adding a solution containing a diamine ligand onto the buffer layer, reacting at 25-35 DEG C for 3-10 days, collecting nanosheets, and dialyzing and purifying the nanosheets to obtain the covalent organic framework nanosheets, (2) taking hydroxyl carbon nanotubes, adding an organic solvent, and carrying out ultrasonic dissolution to obtain a hydroxyl carbon nanotube solution; taking a hydroxyl carbon nanotube solution, mixing the hydroxyl carbon nanotube solution with the covalent organic framework nanosheet obtained in the step (1), performing uniform ultrasonic treatment, performing vacuum pressurization, assembling the mixture onto a nylon membrane, and performing drying to obtain the covalent organic framework composite membrane. The membrane material has excellent properties such as relatively high rejection rate and good antifouling property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of materials, and in particular to a covalent organic framework composite membrane and a preparation method and application thereof. Background Art

[0002] So far, a variety of amorphous polymers have been used to prepare thin films with pore sizes ranging from sub-nanometer to micrometer, such as polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polyethersulfone (PES) and polyimide (PI). However, these amorphous polymer membranes do not have orderly and adjustable pore sizes, have low porosity and poor connectivity, and are not suitable for molecular transport. Therefore, it is of great significance to develop and design new porous crystalline polymer separation membranes with ordered pore structures and adjustable pore sizes.

[0003] Covalent organic framework material is a porous crystalline polymer connected by covalent bonds, which has the characteristics of periodic regular pore structure and excellent chemical resistance and stability, and is an ideal membrane material. Compared with metal organic framework materials (MOF), covalent organic framework materials (COF) have light density, adjustable pore size and fewer defects, so they are more suitable as separation membranes for use in seawater desalination and pollutant separation. With the widespread application of COF membranes, COF membranes with various special functional sites have also attracted attention. Among them, ionic COF membranes are considered to have great potential in separation, ion conduction, sensing, catalysis and energy storage due to their adjustable structure, clear channels and abundant charged sites. The surface interaction between functional materials and guest molecules determines the properties and uses of the materials. Studies have shown that the charge sites on the COF surface will introduce stronger electrostatic forces to the host-guest interaction, thereby opening the door to adjustable properties and functions. Therefore, the present invention selects ionic covalent organic framework materials with different charged sites and carbon nanotubes for doping to prepare composite membranes, and explores their applications in seawater desalination and dye separation.

[0004] CN111540620A discloses a covalent organic framework composite membrane supercapacitor and a preparation method thereof. The method for synthesizing nanosheets in this patent is cumbersome and requires two steps rather than one step. The process of preparing the membrane is complicated and requires first hot dropping the nanosheets onto a carrier and drying them before making a composite membrane with an ionic liquid. The time and cost consumed in the process are higher than those of the present invention. Moreover, the membrane can only be used for gas separation, and its flexibility cannot support its use for liquid separation.

[0005] CN112973468A discloses a method and application for preparing a two-dimensional covalent organic framework ultra-thin nanosheet composite film. The grinding method used in the patent to prepare the COF composite is often affected by a variety of uncertain factors such as the pressure applied by the operator, the grinding speed, and the material of the pestle and mortar. There are too many uncertain factors; the composite film prepared in document 2 needs to be dipped and applied, and it is difficult to achieve uniform thickness of the film. Summary of the invention

[0006] In view of this, the present invention proposes a covalent organic framework composite membrane and its preparation method and application. The present invention selects ionic covalent organic framework materials with different electric potential points and carbon nanotubes for doping to prepare the composite membrane, and the prepared composite membrane has excellent performance.

[0007] The technical solution of the present invention is achieved as follows: A method for preparing a covalent organic framework composite membrane comprises the following steps:

[0008] (1) dissolving 2,4,6-triformylphloroglucinol in an organic solvent to obtain a 2,4,6-triformylphloroglucinol solution;

[0009] Slowly add a buffer layer of deionized water or alkali solution on top of the 2,4,6-triformylphloroglucinol solution;

[0010] Dropping a solution containing a diamine ligand on the buffer layer, reacting at 25 to 35° C. for 3 to 10 days, collecting nanosheets, and dialysis-purifying the nanosheets to obtain covalent organic framework nanosheets;

[0011] (2) taking hydroxyl carbon nanotubes, adding an organic solvent, and ultrasonically dissolving them to obtain a hydroxyl carbon nanotube solution; taking the hydroxyl carbon nanotube solution, and ultrasonically mixing it with the covalent organic framework nanosheets in step (1) to make it uniform, and vacuum pressurizing and assembling them on a nylon membrane, and drying them to obtain a covalent organic framework composite membrane.

[0012] Preferably, in step (1), the solid-liquid ratio of the 2,4,6-triformylphloroglucinol to the organic solvent is 0.1 mmol:80-130 ml; the organic solvent is dichloromethane;

[0013] The volume ratio of the 2,4,6-triformylphloroglucinol solution to the buffer layer is 1:0.2-0.8;

[0014] The alkali solution is a 0.01-0.1M NaOH aqueous solution.

[0015] Preferably, the solution containing the diamine ligand is an ethidium bromide-p-toluenesulfonic acid aqueous solution or a 2,5-diaminobenzoic acid solution.

[0016] Preferably, in step (1), the ethidium bromide-p-toluenesulfonic acid aqueous solution is prepared from ethidium bromide, p-toluenesulfonic acid and water, and the molar volume ratio of the ethidium bromide and p-toluenesulfonic acid to water is 0.1-0.2 mol: 0.25-0.35 mol: 120-140 L;

[0017] The molar ratio of ethidium bromide and p-toluenesulfonic acid to 2,4,6-triformylphloroglucinol is 0.1-0.2:0.25-0.35:0.1.

[0018] Preferably, in step (1), the 2,5-diaminobenzoic acid solution is prepared from 2,5-diaminobenzoic acid and N,N-dimethylformamide, and the molar volume ratio of the 2,5-diaminobenzoic acid to N,N-dimethylformamide is 0.1-0.2 mmol: 40-60 mL.

[0019] Preferably, in step (1), the dialysis purification time is 3 to 4 days.

[0020] Preferably, in step (2), the solid-liquid ratio of the hydroxy carbon nanotubes to the organic solvent is 1 mg: 10-15 ml; and the organic solvent is acetonitrile.

[0021] Preferably, in step (2), the volume ratio of the carbon nanotube solution to the covalent organic framework nanosheets is 1.5-2.5:9-11.

[0022] The covalent organic framework composite membrane described in any one of the embodiments of the present invention is used in seawater desalination or dye separation.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The present invention uses 2,4,6-triformylphloroglucinol and an ion-carrying diamine ligand to react to form a covalent organic framework and a composite membrane with carbon nanotubes. The membrane material has abundant charged points. Due to the electrostatic repulsion between the membrane surface and the solute, it often has a higher interception rate and good anti-fouling performance for solutes with the same negative charge as the composite membrane. It can be applied to the fields of seawater desalination and dye separation. The composite membrane prepared in the present invention is doped with carbon nanotubes, which have high specific strength, strong flexibility, good conductivity and chemical stability, which can improve the performance of the separation membrane, and the substituents on the carbon nanotubes, such as hydroxyl groups, will also interact with the ions to be measured to achieve the purpose of separation.

[0025] (2) At the same time, by comparing the separation performance of different materials, we found that the performance of the composite membrane without charged groups decreased to a certain extent. This may be related to the charge sites on the COF surface. Charged materials have stronger electrostatic forces and have a stronger effect on the ions in the salt solution, thereby achieving the separation purpose.

[0026] (3) Compared with CN111540620A (abbreviated as D1), the main differences from D1 include: the method for synthesizing nanosheets of the present invention includes two methods, not only ball milling method, but also interface method. The interface method in the present invention synthesizes nanosheets only under room temperature conditions and only requires one step of synthesis, and does not require the synthesis of COF powder and then ball milling into nanosheets; the method for preparing composite membranes of the present invention is different from that of D1. The present invention uses vacuum filtration assembly, while D1 uses hot drop method; the application fields are different, the present invention is suitable for salt solution separation, and D1 is suitable for gas separation. The interface method used by the present invention to synthesize nanosheets has mild synthesis conditions and does not require heating to high temperature. The interface method is simpler than D1 in steps, and does not require the synthesis of powder and then ball milling; the composite membrane of the present invention does not require heating, and can be assembled under vacuum decompression, which consumes less energy than D1, and compared with D1, which requires hot drop method and film coating, the filtration assembly steps of the present invention are simpler and easy to prepare.

[0027] (4) Compared with CN112973468A (abbreviated as D2), the main differences from D2 include: the monomers used in D2 to prepare COF materials are different from those of the present invention; D2 uses a grinding method to prepare COF composites, and the present invention uses an interfacial method or a solvent thermal method to prepare COF materials; D2 prepares a composite film by impregnating and smearing the composite onto carbon nanotubes, and the present invention assembles a composite membrane by mixing COF nanosheets with a carbon nanotube dispersion and filtering; the application fields are different, the D2 composite membrane is used for supercapacitors, and the film of the present invention is used for salt solution separation. Compared with D2, the diamine monomers used in the synthesis of COF materials of the present invention basically have electric potential points, so that the surface of the synthesized COF material has charge sites, which can introduce stronger electrostatic force for the interaction between the COF material and the guest molecule, so that the properties and functions of the prepared composite film can be regulated; the process of preparing the COF nanosheet material of the present invention is simple, the synthesis conditions are mild, and the production process is simpler than the grinding method of D2, and does not consume manpower; the surface of the composite film prepared by the present invention is regular and uniform, and compared with D2 which needs to be dipped and coated, the preparation method of the present invention by suction filtration and assembly is easier to adjust the regularity of the surface of the composite film, and the thickness is more uniform. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a reaction mechanism diagram of the covalent organic material prepared using 2,4,6-triformylphloroglucinol and ethidium bromide in Example 1.

[0029] Figure 2 This is the XRD characterization of the covalent organic material prepared by the solvothermal method in comparison group 1.

[0030] Figure 3 This is a physical picture of the covalent organic framework nanosheet solution prepared in Example 1.

[0031] Figure 41 is a particle size diagram and a Zeta potential diagram of the covalent organic framework nanosheet solution prepared in Example 1.

[0032] Figure 5 This is a reaction mechanism diagram of the covalent organic material prepared using 2,4,6-triformylphloroglucinol and 2,5-diaminobenzoic acid in Example 2.

[0033] Figure 6 This is the XRD characterization of the covalent organic material prepared by the solvothermal method in comparison group 2.

[0034] Figure 7 This is a physical picture of the covalent organic framework nanosheet solution prepared in Example 2.

[0035] Figure 8 This is a particle size diagram of the covalent organic framework nanosheet solution prepared in Example 2.

[0036] Fig. 9 This is a reaction mechanism diagram of the covalent organic material prepared using 2,4,6-triformylphloroglucinol and 1,4-phenylenediamine in Comparative Example 1.

[0037] Fig.10 This is the XRD characterization of the covalent organic material prepared by the solvothermal method in Example 1.

[0038] Fig.11 This is a physical picture of the covalent organic framework nanosheet solution prepared in Comparative Example 1.

[0039] Fig.12 This is a particle size diagram of the covalent organic framework nanosheet solution prepared in Comparative Example 1.

[0040] Fig.13 This is a graph showing the relationship between the dilution factor of the nanosheets added to the covalent organic framework composite membrane prepared in Example 1 and the salt rejection rate and flux.

[0041] Fig.14 3 is a graph showing the relationship between the volume of hydroxyl carbon nanotubes added to the covalent organic framework composite membrane prepared in Example 1 and the salt rejection rate and flux.

[0042] In the figure, Intensity: signal intensity; Size: particle size;

[0043] Pemeation flux; osmotic flux; Salt rejection: salt rejection rate. DETAILED DESCRIPTION

[0044] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.

[0045] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.

[0046] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.

[0047] Example 1

[0048] Preparation of TpEB-COF@HCNT composite membrane:

[0049] Step 1, preparation of covalent organic framework nanosheet solution:

[0050] First, 2,4,6-triformylphloroglucinol (Tp) (0.1 mmol, 21.0 mg) dissolved in 130 mL of dichloromethane (DCM) was poured into a beaker to obtain a Tp solution.

[0051] Then, a buffer layer of 80 mL of deionized water was slowly added on top of the Tp solution.

[0052] Finally, ethidium bromide (EB) (0.15mmol, 59.2mg) and p-toluenesulfonic acid (PTSA) (0.3mmol, 57.1mg) were dissolved in 130mL of water and slowly added to the buffer for 50min. Stored at 35℃ for 10 days without interference. The top water layer was removed with a dropper, and the nanosheets formed at the interface were collected. The TpEB-COF nanosheets were dialyzed and purified for 3 days. The structure and physical properties of TpEB-COF nanosheets are shown in Figure 2. Figure 1 , Figure 3 As shown; the particle size and Zeta potential were tested. Figure 4 shown.

[0053] Step 2, preparation of covalent organic framework composite membrane: weigh 1 mg of hydroxy carbon nanotube (HCNT), add 10 ml of acetonitrile, and dissolve by ultrasonication. Take 2 ml of the prepared carbon nanotube solution, mix it with 10 ml of covalent organic framework nanosheets by ultrasonication, assemble it on the nylon membrane by vacuum pressure, and store it by drying at room temperature to obtain TpEB-COF@HCNT composite membrane.

[0054] The relationship between the dilution factor of the nanosheets added to the TpEB-COF@HCNT composite membrane and the salt rejection rate and flux was tested using a cross-flow filtration flat membrane tester. Fig.13 As shown. The left side shows the salt rejection rate of the covalent organic framework composite membrane for 1mM Na2SO4 solution, and the right side shows the permeation flux of 1mM Na2SO4 solution. Take 10mL of the nanosheet solution and dilute it with deionized water. The volume proportions of the nanosheets are 0.2, 0.4, 0.6, 0.8 and 1 respectively. The membranes are assembled by vacuum pressurization and tested. The test pressure is 0.60MPa, the temperature is 23℃, and the effective test area is 0.9cm 2As the dilution factor of the nanosheets decreases, the salt rejection rate of the assembled membrane increases and the permeation flux decreases.

[0055] The relationship between the volume of hydroxyl carbon nanotubes added to the TpEB-COF@HCNT composite membrane and the salt rejection rate and flux was tested using a cross-flow filtration flat membrane tester. Fig.14 As shown. The left side shows the salt rejection rate of the covalent organic framework composite membrane for 1mM Na2SO4 solution, and the right side shows the permeation flux of 1mM Na2SO4 solution. 0mL, 1m, 2mL and 3mL of hydroxy carbon nanotube solution and 10mL of TpEB-COF nanosheets were respectively taken for vacuum pressurization to assemble into membranes and tested at a test pressure of 0.60MPa and a temperature of 23°C.

[0056] The results show that the salt rejection rate and permeation flux of the TpEB-COF@HCNT composite membrane are related to the concentration of TpEB-COF nanosheets. The same amount of nanosheets were diluted to different concentrations by deionized water. As the concentration of nanosheets increased, the salt rejection rate of the composite membrane increased accordingly, but the permeation flux decreased with the increase of nanosheet concentration. This may be related to the stacking of nanosheets. Under vacuum pressure, the nanosheets with high concentrations are stacked more tightly, and the gaps between layers are smaller. At the same time, the TpEB-COF channels are staggered and stacked, and are affected by the electrostatic effect of the charged groups on the channels, which is not conducive to the passage of salt ions. Therefore, the salt rejection rate increases and the corresponding solution passage rate decreases.

[0057] The salt rejection rate and permeation flux of the TpEB-COF@HCNT composite membrane are also related to the amount of doped hydroxyl carbon nanotubes. As the volume of added hydroxyl carbon nanotubes increases to 2mL, the salt rejection rate of the composite membrane gradually increases until 95%, at which point the salt rejection rate reaches the highest. Then, when 3mL of hydroxyl carbon nanotubes are doped, the salt rejection rate drops sharply. On the contrary, the permeation flux of the composite membrane rises sharply at this time. This may be related to the accumulation of hydroxyl carbon nanotubes. When hydroxyl carbon nanotubes are doped to 2mL, a good equilibrium relationship is maintained between the carbon nanotubes and the TpEB-COF nanosheets, and the interaction between the charged groups reaches equilibrium until the hydroxyl carbon nanotubes continue to increase, destroying the electrostatic force balance between the two, causing the salt rejection rate to drop sharply.

[0058] Comparison group 1

[0059] Preparation of TpEB-COF powder by solvothermal method: 2,4,6-triformylphloroglucinol (0.1mmol, 21mg) and ethidium bromide (0.15mmol, 59.15mg) were added to a Pyrex tube, and then 0.5mL of 1,4-dioxane and mesitylene were added, ultrasonic dispersion was performed for 15 minutes, acetic acid solution (6M, 0.1mL) was added, and the mixture was placed in a liquid nitrogen bath (77K), and freeze-degassing-thawing cycles were repeated 3 times. The tube was sealed with a high-temperature flame, and the Pyrex tube was placed in a 120°C oven for 3 days. After cooling to room temperature, the solid powder was filtered, washed with tetrahydrofuran, and vacuum dried at 120°C to obtain a covalent organic framework material powder. The reaction mechanism corresponds to Figure 1 . Further characterization of its XRD results are as follows Figure 2 shown.

[0060] The results show that the TpEB-COF powder prepared by the solvothermal method has a good crystal form and is the same substance as the synthesized TpEB-COF nanosheets. The TpEB-COF nanosheets prepared by step 1 of Example 1 of the present invention can reduce energy consumption and effectively reduce costs while maintaining a good crystal form.

[0061] Example 2

[0062] Preparation of TpPa-COOH-COF@HCNT composite membrane:

[0063] Step 1, preparation of covalent organic framework nanosheet solution:

[0064] First, 2,4,6-triformylphloroglucinol (Tp) (0.1 mmol, 21.0 mg) dissolved in 80 mL of dichloromethane (DCM) was poured into a beaker to obtain a Tp solution.

[0065] Then, a buffer layer of 20 mL of 0.05 M NaOH aqueous solution was slowly added on top of the Tp solution.

[0066] Finally, 2,5-diaminobenzoic acid (0.15mmol, 22.82mg) was dissolved in 50mL N,N-dimethylformamide (DMF). The mixture was allowed to stand at 25°C for 3 days without interference. The obtained system was dropped into 20mL deionized water and then extracted to obtain nanosheets dissolved in water. The nanosheets were purified by dialyzing in deionized water for 3 days. A transparent aqueous solution of nanosheets was obtained. The structure and physical properties of TpPa-COOH-COF nanosheets are shown in Figure 2. Figure 5 , Figure 7 As shown; the particle size test is carried out, such as Figure 8 shown.

[0067] Step 2, preparation of covalent organic framework composite membrane: weigh 1 mg of hydroxy carbon nanotubes, add 10 ml of acetonitrile, and dissolve by ultrasonication. Take 2 ml of the prepared carbon nanotube solution, mix it with 10 ml of covalent organic framework nanosheets by ultrasonication, assemble it on the nylon membrane by vacuum pressure, and store it by drying at room temperature to obtain TpPa-COOH-COF@HCNT composite membrane.

[0068] The results show that the present invention successfully synthesized and prepared TpPa-COOH-COF nanosheets and

[0069] TpPa-COOH-COF@HCNT composite membrane. The types of composite membranes with charged groups have been successfully expanded, which is in contrast to the uncharged TpPa-COF@HCNT composite membrane, thus highlighting the important role of ionic covalent organic framework composite membranes in the application field of seawater desalination.

[0070] Comparison group 2

[0071] Preparation of TpPa-COOH-COF powder by solvothermal method: 2,4,6-triformylphloroglucinol (0.05mmol, 10.5mg) and 2,5-diaminobenzoic acid (0.075mmol, 11.41mg) were added to a Pyrex tube, and then 0.8mL of o-dichlorobenzene and 0.2mL of N,N-dimethylacetamide were added, and ultrasonic dispersion was performed for 15 minutes, and acetic acid solution (6M, 0.1mL) was added, and the mixture was placed in a liquid nitrogen bath (77K), and the mixture was freeze-degassing-thawing cycled for 3 times, and the tube was sealed with a high-temperature flame, and finally the Pyrex tube was placed in a 120°C oven for 3 days. After cooling to room temperature, the solid powder was filtered, washed with tetrahydrofuran, and vacuum dried at 120°C to obtain a covalent organic framework material powder, and its reaction mechanism corresponds to Figure 5 . Further characterization of its XRD results are as follows Figure 6 shown.

[0072] The results show that the TpPa-COOH-COF powder prepared by the solvothermal method has a good crystal form and is the same substance as the synthesized TpPa-COOH-COF nanosheets. The TpPa-COOH-COF nanosheets prepared by step 1 of Example 2 of the present invention can reduce energy consumption and effectively reduce costs while maintaining a good crystal form.

[0073] Comparative Example 1

[0074] Preparation of TpPa-COF@HCNT composite membrane:

[0075] Step 1, preparation of TpPa-COF powder by solvothermal method: 2,4,6-triformylphloroglucinol (0.3mmol, 63mg) and 1,4-phenylenediamine (0.45mmol, 48mg) were added to a Pyrex tube, and then 1.5mL of 1,4-dioxane and mesitylene were added, ultrasonic dispersion was performed for 15 minutes, acetic acid solution (3M, 0.5mL) was added, and the mixture was placed in a liquid nitrogen bath (77K), and freeze-degassing-thawing cycles were repeated 3 times. The tube was sealed with a high-temperature flame, and the Pyrex tube was placed in a 120°C oven for 3 days. After cooling to room temperature, the solid powder was filtered, washed with tetrahydrofuran, and vacuum dried at 120°C to obtain a red covalent organic framework material powder, and its reaction mechanism corresponds to Fig. 9 . Further characterization of its XRD results are as follows Fig.10 shown.

[0076] Step 2, prepare covalent organic framework nanosheet solution: use top-down ultrasonic assisted liquid phase exfoliation method to exfoliate the covalent organic framework material COF powder. The specific steps are: first manually grind the covalent organic framework material powder that has been synthesized in step 1 into fine powder, take 50 mg of the ground powder, add 5 ml of anhydrous ethanol solution, and place it in a ball mill for exfoliation for 3 hours. After the exfoliation is completed, ultrasonically disperse it in an ultrasonic instrument, centrifuge it at 6000r / min, and take the supernatant. Let it stand for more than 24 hours, filter out the excess COF particles in the system, and obtain a nanosheet suspension, that is, a covalent organic framework nanosheet solution (TpPa-COF nanosheet). The structure of TpPa-COF nanosheets and the actual object are as follows Fig. 9 , Fig.11 As shown; the particle size test is carried out, such as Fig.12 shown.

[0077] Step 3, preparation of covalent organic framework composite membrane: weigh 1 mg of hydroxy carbon nanotubes, add 10 ml of acetonitrile, ultrasonically dissolve, and obtain a carbon nanotube solution. Take 2 ml of the prepared carbon nanotube solution, mix it with 10 ml of the covalent organic framework nanosheets in step 2 by ultrasonic uniformity, assemble it on the nylon membrane by vacuum pressure, and dry it at room temperature to obtain a TpPa-COF@HCNT composite membrane.

[0078] The results show that the comparative example successfully synthesized and prepared TpPa-COF nanosheets and TpPa-COF@HCNT composite membranes, with an average particle size of about 229nm. The experimental results show that the salt rejection rate of the TpPa-COF@HCNT composite membrane is significantly lower than that of the composite membrane with charged groups. This may be related to the charged points on the pores of the composite membrane. Since there is an electrostatic interaction between the surface of the composite membrane with charged groups and the salt ions, the salt rejection performance is significantly improved. However, there are no charged functional groups on the pores of the TpPa-COF@HCNT composite membrane, which leads to significant differences from the experimental results of the former.

[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a covalent organic framework composite membrane, characterized in that: The following steps are involved: (1) dissolving 2,4,6-triformylphloroglucinol in an organic solvent to obtain a 2,4,6-triformylphloroglucinol solution; Slowly add a buffer layer of deionized water or alkali solution on top of the 2,4,6-triformylphloroglucinol solution; Dropping a solution containing a diamine ligand on the buffer layer, reacting at 25 to 35° C. for 3 to 10 days, collecting nanosheets, and dialysis-purifying the nanosheets to obtain covalent organic framework nanosheets; (2) taking hydroxyl carbon nanotubes, adding an organic solvent, and ultrasonically dissolving them to obtain a hydroxyl carbon nanotube solution; taking the hydroxyl carbon nanotube solution, and ultrasonically mixing it with the covalent organic framework nanosheets in step (1) to make it uniform, and vacuum pressurizing and assembling them on a nylon membrane, and drying them to obtain a covalent organic framework composite membrane.

2. The method for preparing a covalent organic framework composite membrane according to claim 1, characterized in that: Step (1), the solid-liquid ratio of the 2,4,6-triformylphloroglucinol to the organic solvent is 0.1mmol:80-130ml; The organic solvent is dichloromethane; The volume ratio of the 2,4,6-triformylphloroglucinol solution to the buffer layer is 1:0.2-0.8; The alkali solution is a 0.01-0.1M NaOH aqueous solution.

3. The method for preparing a covalent organic framework composite membrane according to claim 1, characterized in that: The solution containing the diamine ligand is an ethidium bromide-p-toluenesulfonic acid aqueous solution or a 2,5-diaminobenzoic acid solution.

4. The method for preparing a covalent organic framework composite membrane according to claim 1, characterized in that: Step (1), the ethidium bromide-p-toluenesulfonic acid aqueous solution is prepared from ethidium bromide, p-toluenesulfonic acid and water, and the molar volume ratio of the ethidium bromide, p-toluenesulfonic acid and water is 0.1-0.2 mol: 0.25-0.35 mol: 120-140 L; The molar ratio of ethidium bromide and p-toluenesulfonic acid to 2,4,6-triformylphloroglucinol is 0.1-0.2:0.25-0.35:0.

1.

5. The method for preparing a covalent organic framework composite membrane according to claim 1, characterized in that: In step (1), the 2,5-diaminobenzoic acid solution is prepared from 2,5-diaminobenzoic acid and N,N-dimethylformamide, and the molar volume ratio of the 2,5-diaminobenzoic acid to N,N-dimethylformamide is 0.1-0.2 mmol: 40-60 mL.

6. The method for preparing a covalent organic framework composite membrane according to claim 1, characterized in that: In step (1), the dialysis purification time is 3 to 4 days.

7. The method for preparing a covalent organic framework composite membrane according to claim 1, characterized in that: In step (2), the solid-liquid ratio of the hydroxy carbon nanotubes to the organic solvent is 1 mg: 10-15 ml; and the organic solvent is acetonitrile.

8. The method for preparing a covalent organic framework composite membrane according to claim 1, characterized in that: In step (2), the volume ratio of the carbon nanotube solution to the covalent organic framework nanosheets is 1.5-2.5:9-11.

9. A covalent organic framework composite membrane, characterized in that: The method is prepared according to any one of claims 1 to 8.

10. Use of the covalent organic framework composite membrane according to any one of claims 1 to 8 in seawater desalination or dye separation.

Citation Information

Patent Citations

  • Covalent organic framework composite film supercapacitor and preparation method

    CN111540620A

  • Method for preparing two-dimensional covalent organic framework ultrathin nanosheet material composite film and application of two-dimensional covalent organic framework ultrathin nanosheet material composite film

    CN112973468A

  • Two-dimensional oximidation covalent organic framework electrode membrane and preparation method and application thereof

    CN114887492A

  • Ligand, covalent organic framework material, SWCNT / COF-ET59 composite film and application

    CN115286516A

  • Nanofiltration membrane as well as preparation method and application thereof

    CN117160248A

Cited By

  • Filtering assembly capable of being internally and externally cleaned, dynamic membrane module device and cleaning method

    CN120191996A

  • Internally and externally cleanable filter assembly, dynamic membrane module, and cleaning method

    CN120191996B